Impact of conditional cash transfer on households food security in Akwa Ibom State, Nigeria - Otu W. Ibok; Iniobong E. Okon; Oscar P. Akpan; Imefon F. Isip (PLoS ONE, 2025)
The Nigerian government introduced the Household Upliftment Program (HUP) which is a conditional cash transfer scheme to help households improve consumption levels, reduce poverty and therefore prevent vulnerable households from becoming poorer. This paper investigated the impact of Condition Cash Transfer of HUP on household food security in Akwa Ibom State, Nigeria. The objectives were to assess the impact of CCT on protecting the beneficiary’s basic level of food consumption from becoming food insecure and also determine if CCT of HUP facilitate the beneficiary to invest in human and other productive assets. The paper utilized descriptive statistics, food security index, Likert scale and propensity score technique to analyse the research objectives. The findings showed that on average, benefitting and non-benefitting households spent about N31,917.78 ($76.46) and N34,898.67 ($83.60) respectively on food per month. Food insecurity was higher among benefiting households compared to non-benefiting households. The Average Treatment Effect on the Treated (ATET) estimator value was −0.2610. The negative value suggests that, on average, benefiting households spend 26.10% less on food consumption than non-benefitting households. The results imply that the current cash transfer program may not be effectively addressing food insecurity among beneficiaries. However, the CCT program facilitated the beneficiaries’ ability to invest in human and productive assets, enhanced their financial and social inclusion, opened doors to financial services previously inaccessible to many and fostered a sense of community among them. The paper concludes that while conditional cash transfer programs have the potential to positively impact beneficiaries, the government must reassess and potentially adjust the program to better address the current inflationary pressures and ensure its positive impact on the food security of the beneficiaries.